Районна, обласна рада в системі місцевого самоврядування України - Бальций Юрій Юрійович; Бальций Юрий Юрьевич; Bal'cij Jurij (My University, 2012)
Àrticle is devoted research of regula-tion of district, regional councils by the Law of Ukraine «On local self-govern-ment in Ukraine». Noted that the system of local councils as representative bod-ies of local self-government consists of two subsystems — the base and regional levels. The basic directions of perfection of the constitutional bases of the orga-nization and functioning of district and regional councils in Ukraine.
Бальций Ю. Районна, обласна рада в системі місцевого самоврядування України / Ю. Бальций // Юридичний вісник. - 2012. - № 2. - С. 37-40.
Keywords: місцеве самоврядування; система місцевого самоврядування; компетенція; реформа; районна рада; обласна рада; местное самоуправление; система местного самоуправления; компетенция; районный совет; областной совет; local government; system of local government; competence; reform; District Council; regional Council